Expression of group II and III mGluRs in the carotid body and its role in the carotid chemoreceptor response to acute hypoxia - Zhao, Chenlu; Li, Chaohong; Zhao, Baosheng; Liu, Yuzhen (Frontiers in Physiology, 2022)
The carotid body (CB) contributes significantly to oxygen sensing. It is unclear, however, whether glutamatergic signaling is involved in the CB response to hypoxia. Previously, we reported that inotropic glutamate receptors (iGluRs) and multiple glutamate transporters are present in the rat CB. Except for iGluRs, glutamate receptors also include metabotropic glutamate receptors (mGluRs), which are divided into the following groups: group I (mGluR1/5); group II (mGluR2/3); group III (mGluR4/6/7/8). We have studied the expression of group I mGluRs in the rat CB and its physiological function response to acute hypoxia. To further elucidate the states of mGluRs in the CB, this study’s aim was to investigate the expression of group II and III mGluRs and the response of rat CB to acute hypoxia. We used reverse transcription-polymerase chain reaction (RT-PCR) to observe mRNA expression of GRM2/3/4/6/7/8 subunits by using immunostaining to show the distribution of mGluR2 and mGluR8ng. The results revealed that the GRM2/3/4/6/7/8 mRNAs were expressed in both rat and human CB. Immunostaining showed that mGluR2 was localized in the type I cells and mGluR8 was localized in type I and type II cells in the rat CB. Moreover, the response of CB to acute hypoxia in rats was recorded by in vitro carotid sinus nerve discharge. Perfusion of group II mGluRs agonist or group III mGluRs agonist (LY379268 or L-SOP) was applied to examine the effect of group II and III mGluRs on rat CB response to acute hypoxia. We found that LY379268 and L-SOP inhibited hypoxia-induced enhancement of CSN activity. Based on the above findings, group II and III mGluRs appear to play an inhibitory role in the carotid chemoreceptor response to acute hypoxia.